Economic complexity, FinTech, green innovation, and environmental degradation in emerging markets - Ageli, Mohammed Moosa (Frontiers in Environmental Science, 2025)
IntroductionEnvironmental degradation has emerged as a significant concern in recent decades, particularly for developing nations. The study examines the dynamic relationship between economic complexity, FinTech, green innovation, and environmental degradation in emerging economies.MethodsTo achieve the study objectives, the study employs a robust estimate, namely MMQR, which incorporates FMOLS and DOLS, for the period from 1990 to 2024.ResultsThe findings suggest that economic complexity and FinTech play a role in promoting cleaner manufacturing and expanding access to green financial services, thereby enhancing environmental sustainability. The adoption of green innovation mitigates environmental deterioration, albeit to varying degrees, across different emissions intensities. In addition, the results of the co-integration test revealed a long-run correlation between the variables ECI, GIN, and FT, and CO2 emissions. The slope heterogeneity test results indicate considerable variance in the relationships between emerging economies. This highlights the fact that crucial variables differ significantly across countries.DiscussionThe study contributes to the debate on the green transition in emerging economies, providing policymakers with solid data for balancing economic growth and environmental protection. The research also reveals that institutional and technical restrictions in emerging economies may limit or even harm these drivers in lower quantiles. These results highlight the importance of tailoring green growth programs to specific environmental settings and quantile levels.